Geodetske evidence kot povezovalni člen med lastnino in prostorom - Vugrin, Marijana (Geodetski vestnik, 2011)
This article considers the placement of ownership rights into space, possible only with the help of the land cadastre graphical representation. A definitionof trust for locating property rights on the land cadastre graphic presentation is given as well as a way of determining it. The ownership concept of the Republic of Slovenia is also defined, the knowledge of which isrelevant to ownership rights placement. Discrepancies found in the Information of Test Property Value Calculation formed because of a false placement of rights are also stated. We especially focused on the link betweena parcel and building and studied a pattern of 1,784 buildings that were equally distributed throughout Slovenia.
Keywords: cadastre; etažna lastnina; floor ownership; information of test property value calculation; land cadastre; land cadastre graphical presentation; land registry; lastninska pravica; level of trust; obveščanje o poskusnem izračunu vrednosti nepremičnin; ownership; parcel; parcela; stopnja zaupanja; zemljiška knjiga; zemljiški kataster; zemljiškokatastrski prikaz